2023
DOI: 10.3390/ma16145200
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Investigation of Properties of Metallic Parts Additively Manufactured through MEX and PBF-LB/M Technologies

Abstract: In this study, the research on 316L steel manufactured additively using two commercially available techniques, Material Extrusion (MEX) and Laser Powder Bed Fusion of Metals (PBF-LB/M), were compared. The additive manufacturing (AM) process based on powder bed synthesis is of great interest in the production of metal parts. One of the most interesting alternatives to PBF-LB/M, are techniques based on material extrusion due to the significant initial cost reduction. Therefore, the paper compares these two diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Several studies have set out to determine optimal print parameters, varying nozzle temperature, infill strategy, build orientation, print speed, extrusion multiplier, line width, and layer height [12,13]. The effects of print parameters on shrinkage during processing [12,[14][15][16], geometric accuracy [16], density [12,17,18], tension tests [8,[13][14][15]18,19], optimization of post-processing [20], fatigue [21], hardness [14,18,22], and surface roughness [22] have been investigated, often comparing to samples produced from L-PBF [19,22], other MEX processes such as Desktop Metal and Markforged [21,22] or samples from conventionally manufactured 316L plate [8,14]. Typically industrial or commerical grade FFF printers have been utilized in previous research.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have set out to determine optimal print parameters, varying nozzle temperature, infill strategy, build orientation, print speed, extrusion multiplier, line width, and layer height [12,13]. The effects of print parameters on shrinkage during processing [12,[14][15][16], geometric accuracy [16], density [12,17,18], tension tests [8,[13][14][15]18,19], optimization of post-processing [20], fatigue [21], hardness [14,18,22], and surface roughness [22] have been investigated, often comparing to samples produced from L-PBF [19,22], other MEX processes such as Desktop Metal and Markforged [21,22] or samples from conventionally manufactured 316L plate [8,14]. Typically industrial or commerical grade FFF printers have been utilized in previous research.…”
Section: Introductionmentioning
confidence: 99%
“…Typically industrial or commerical grade FFF printers have been utilized in previous research. Industrial printers such as the Apium P155 ($10,000-$25,000+) or commercial grade such as the Creatbot F430 [16], Lulzbot TAZ6 [20], Intamsys Funmat HT [19], Ultimaker S5 [12], Ultimaker 3 [13] ($2000-$10,000), or consumer grade such as Felix Tec 4 [15] and Prusa i3 [8,22] ($1000-$2000) have been utilized. At present, no studies have utilized any of the common hobbyist grade printers available for under $500.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Qualitative and quantitative analysis of the pores in the green and sintered parts using micro-tomography confirmed that the optimized printing parameters were beneficial for the final microstructure. In addition, several researchers have also investigated the FDM process of other metallic or ceramic materials; for example, 316L [25][26][27], 17-4PH [28,29], copper [30,31], hardmetal [32], Ti6Al4V [33,34], tungsten heavy alloy [35], H13 [36], Al [37], 1.2083 steel [38], zirconia [39,40], etc. However, no studies on the FDM of 15-5PH stainless steel (15-5PH SS) materials were found in the available literature.…”
Section: Introductionmentioning
confidence: 99%
“…Appropriate heat treatment can reduce dislocations and increase precipitates significantly, which provides the possibility to make printed 316L SS comparable to conventional technologies [27]. Compared with conventional material extrusion, laser powder-bed fusion can also provide lower porosity and higher hardness [28]. Inconel 718 parts manufactured with the machining process of LMD are also found to be different from the forged workpiece in chip geometry and bending moment [29].…”
Section: Introductionmentioning
confidence: 99%